Students’ Online Information Searching Strategies and Their Creative Question Generation: The Moderating Effect of Their Need for Cognitive Closure - Mao, Shibo; Wang, Di; Tang, Chaoying; Dong, Pinhua (Frontiers in Psychology, 2022)
With the wide application of computers and digital technologies, online information searching is being integrated into students’ learning process. Improving students’ creative question generation through online information searching is an emerging research topic in creativity and pedagogy field. Online information searching brings diversified information but it also leads to cognitive load brought by a large amount of online information. Using online information searching to generate creative question depends on students’ cognitive properties. However, the existing literature ignores the joint influence of students' online information searching strategies and cognitive properties on their creative question generation. This study puts forward three hypotheses: first, the two strategies of students’ online information searching (‘keywords’ and ‘Web page exploration’) will increase their creative question generation; Second, the impact of ‘keywords’ is negatively moderated by students’ need for cognitive closure (NFCC); Third, the impact of ‘Web page exploration’ is positively moderated by NFCC. The main reason is that high NFCC prevents students obtaining diversified perspectives by using different keywords, but it helps to avoid distraction caused by a large amount of online information and promote the persistency of their reading information. Based on the data of quasi-experimental tasks completed by 90 students in grade 7 and grade 8, the results support the above hypothesis. The contributions of creative question generation theory and NFCC theory, as well as important issues of future study are discussed.